Investigation of hydrogen embrittlement in steel alloys: mechanism, factors, advanced methods and materials, applications, challenges, and future directions: A review - Umme Javeria; Sung Jin Kim (Journal of Materials Research and Technology)
Hydrogen embrittlement (HE) remains a critical challenge in structural metals, particularly steels, compromising their mechanical integrity in hydrogen-containing environments. The process typically initiates with crack nucleation and progresses to fracture due to a reduction in ductility and an increase in brittleness. This poses serious reliability concerns for industries, such as the automotive, oil and gas, and construction industries, that heavily rely on steel structures. To effectively address this issue, it is essential to first understand the underlying mechanisms and influencing factors of HE, which inform the development of appropriate mitigation strategies. Researchers have explored various mitigation methods, including the application of metallic or ceramic coatings, microstructural optimization, and alloying approaches. This review provides a comprehensive overview of i) the mechanisms of HE in both surface and bulk regions of steel, ii) the factors influencing the severity of HE, iii) advanced analytical approaches–such as thermal desorption spectroscopy (TDS), density functional theory (DFT), machine learning (ML) atom probe tomography (APT), and others–for elucidating HE mechanisms, iv) effective methods to prevent or minimize HE, and v) practical applications in automotive, oil and gas, and marine structures. Lastly, this review critically discusses the major challenges currently faced by the steel industry and outlines potential solutions and future research directions.